Development of ship propeller using dynamic casting method - Mohmad Ali, Ishak (2016)
The ship propeller is a key component in producing the propulsion force of the ship motion. Therefore, the stability of structure strength is required to ensure the effectiveness of propulsion force generation. This research examines the existing ship propeller and the effects of dynamics casting mold on the changes of mechanical properties of the propeller structure. The specimen prepared is referred to ASTM E8 2008 standard and including two projections is Longitude and Latitude projected, according to the forces analysis exerted on blade structure. The experiments perform on the used propeller and casted specimen in order to verify the projections arrangement of changes in mechanical properties. The results show that the different of used propeller and casted specimen properties is less than 5% and the arrangement can be represented for dynamics casting analysis. The dynamics mold used are Centrifugal Mold and Vibration Mold with selection of centrifugal speeds are 0, 50rpm and 150rpm and the vibration frequencies are 0, 5Hz and 9Hz,respectively. The mechanical testing is conducted on tensile test, hardness test and scanning electron microscope investigation. The result of casting experiment showed that the mechanical properties significantly increased by the vibration frequencies up to 9Hz and the centrifugal speed up to 150rpm and led to increase in tensile strength from 4.84% to 9.68% for vibration mold and from 1.70% to 14.86% for centrifugal mold, respectively. In the vibration mold casting, the tensile strength, yield strength and elongation percentage showed the approximation of the properties values of matching the frequency of vibration is over than 9Hz on both projections but not in the centrifugal mold. It was also found that hardness improved significantly with the increased in vibration frequency and centrifugal speed. The hardness value based Rockwell superficial 15N-S scale is 6% over than without vibration. In addition, the change in microstructure and mechanical properties were successfully represented by the changes in solidification characteristics. Various vibration frequencies have reduced the lamellar spacing that changes the microstructure of the composites which as a result became more fibrous. The corresponding changes in mechanical properties indicate that the vibration casting method significantly increased the mechanical properties of casted propeller and it should be applied as a method in ship propeller manufacturing on casting process.